Evaluation of a participatory action project to improve safety and outcomes in maternity care - Marie-Clare Balaam; Gill Thomson (Health Research Policy and Systems)
Abstract Background Maternal violence, in terms of obstetric violence and/or the disrespect and abuse of women and birthing people accessing maternity care, is a global concern. This mistreatment and experience of maternal violence and harm has negative physical and psychological impacts on women, birthing people and their babies. This paper evaluates a multipartner project which aimed to co-produce specialist resources to support women and birthing people who had experienced violence and harm. The evaluation sought to understand the collaborative and co-production processes employed and to identify recommendations and learning from the project. Methods An ethnographic-based evaluation based on action research and participatory action research principles was undertaken using qualitative interviews, documentary review and observations. The data were analysed using reflexive thematic analysis. Results A total of 18 interviews were conducted with 21 participants from the lead, project partner and onward grant recipient organizations. In addition, 80 documents were reviewed, and 9 collaborative group meetings and 2 in-person events were observed. Factors which supported and inhibited effective collaborative working and co-production were identified in five aspects: ensuring inclusivity, clarity and transparency, building and maintaining relationships, collaboration and cooperation and active learning. Conclusions Effective collaborative co-production needs to consider issues of inclusivity and diversity and to ensure clarity and transparency in terms of remit, commitments and finances. Building and maintaining relationships between partners and communities by creating a safe space for participation and inclusive leadership was crucial. Recommendations from the evaluation include the need to ensure mechanisms for clear communication within projects from their inception as well as the need to acknowledge and proactively address issues of diversity and inclusivity throughout all aspects of the co-production process to support the fullest participation from diverse stakeholders.